Causality Orientations and Supportive/Controlled Environment: Understanding Their Influence on Basic Needs, Motivation for Health and Emotions in French Hospitalized Older Adults - Souesme, Guillaume; Martinent, Guillaume; Akour, Donia; Giraudeau, Caroline; Ferrand, Claude (Frontiers in Psychology, 2020)
Objectives: Based on the self-determination theory, the purpose of the present study was to better understand how to motivate hospitalized older adults’ behaviors and test an integrative model of the role of causality orientations and a supportive/controlled environment on basic need satisfaction, motivation for health oriented physical activity, positive and negative affective states, depressive symptoms, apathy and boredom. Methods: Older people (N=146; Mage=81.27 years, SD=7.75, 74.7% female) in French hospital units completed self-report questionnaires and socio-demographic data were also collected. Results: Partial least squares path modeling results showed that participants’ autonomy orientation positively associated with the perception of a supportive environment leads to need satisfaction, autonomous motivation for health-oriented physical activity and high scores on positive affective states. Conversely, participants’ impersonal orientation positively associated with the perception of a controlled environment leads to undermining need satisfaction, controlled motivation for health-oriented physical activity and amotivation and high scores on both negative affective states and boredom. Conclusion: The present results indicate that taking into account personality factors in hospital units can be useful and health professionals should take an interest both in the patients’ causality orientations and the supportive nature of the environment in order to understand better how to motivate patients’ behaviors. The present study points to the need to focus on all motivational dynamics which allow patients’ supporting